Perbedaan Pola Asuh dan Tingkat Kecukupan Zat Gizi pada Balita Stunting dan Non-Stunting di Wilayah Pesisir Kabupaten Probolinggo - Mita Femidio; Lailatul Muniroh (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: Stunting was still found in coastal areas, whereas people there had greater opportunities to consume fish which is contain high animal protein to prevent stunting.Objectives: To analyze differences in parenting and nutrient adequacy level on stunting and non-stunting toddlers in the coastal area of Probolinggo District.Methods: This study was a case-control design, which conducted in the village of Pajurangan included Puskesmas Gending. The total sample were 46 toddlers (24-59 months old) divided into cases group (stunting) and control group (non-stunting) with each of group 23 toddlers, that chosen by simple random sampling method from 194 population of toddlers. Data collection included toddler height measurements with microtoise by researchers as well as the questionnaires parenting and SQ-FFQ. Data were analyzed using the Chi-Square test by Odds Ratio (OR).Results: 60.9% stunting group have parenting feeding medium category, but parenting basic health care have good parenting category (91.3%). Most of adequacy level of energy (60.9%), protein (65.2%) and zinc (56.5%) in stunting group were less category, whereas vitamin A was enough category (65.2%).Therefore, there were differences in parenting feeding (p=0.002; OR=10.37; 95%CI=2.374-45.301) and energy adequacy level (p=0.037; OR=4.407; 95%CI=1.26-15.414), protein (p=0.001; OR=12.5; 95%CI=2.828-55.254) and zinc (p=0.015; OR=6.175; 95%CI=1.589-23.993) on stunting and non-stunting toddlers. However, there were no differences in parenting basic health care (p=0.662) and adequacy of vitamin A (p=0.314) on stunting and non-stunting toddlers.Conclusions: Improper parenting and toddler with inadequate levels of energy, protein and zinc had greater risk of stunting compared to toddlers suffered enough. ABSTRAK Latar Belakang: Stunting masih terjadi di daerah pesisir, padahal masyarakat tersebut memiliki peluang lebih besar mengkonsumsi ikan yang kaya protein sehingga dapat mencegah stunting.Tujuan: Menganalisis perbedaan pola asuh dan tingkat kecukupan zat gizi pada balita stunting dan non-stunting di wilayah pesisir Kabupaten Probolinggo.Metode: Desain studi yang digunakan adalah case-control. Penelitian dilakukan di desa pesisir yaitu Desa Pajurangan, wilayah kerja Puskesmas Gending. Total sampel adalah 46 subjek balita berusia 24-59 bulan, terbagi menjadi 23 balita kelompok stunting dan 23 balita kelompok non-stunting. Pengambilan sampel menggunakan metode simple random sampling dari total populasi 194 balita. Pengumpulan data meliputi pengukuran tinggi badan balita dengan mikrotoa oleh peneliti serta wawancara kuesioner pola asuh dan Semi Quantitative Food Frequency Questionnare (SQ-FFQ). Data dianalisis menggunakan uji Chi-Square dengan melihat Odds Ratio (OR).Hasil: 60,9% kelompok stunting memiliki pola asuh pemberian makan kategori sedang, sedangkan pola asuh perawatan kesehatan dasar kategori baik (91,3%). Tingkat Kecukupan energi (60,9%), protein (65,2%) dan seng (56,5%) pada kelompok stunting kategori kurang, sedangkan vitamin A kategori cukup (65,2%). Terdapat perbedaan pola asuh pemberian makan (p=0,002; OR=10,37; 95%CI=2,374-45,301), tingkat kecukupan energi (p=0,037; OR=4,407; 95%CI=1,26-15,414), protein (p=0,001; OR=12,5; 95%CI=2,828-55,254) dan seng (p=0,015; OR=6,175; 95%CI=1,589-23,993) pada balita stunting dan non-stunting. Tidak terdapat perbedaan pola asuh perawatan kesehatan dasar (p=0,662) dan tingkat kecukupan vitamin A (p=0,314) pada balita stunting dan non-stunting.Kesimpulan: Pola asuh pemberian makan serta tingkat kecukupan energi, protein dan seng yang kurang berisiko lebih besar balitanya mengalami stunting dibanding kelompok yang cukup